STRATEGI GURU AQIDAH AKHLAK DALAM MENANAMKAN NILAI-NILAI PENDIDIKAN KARAKTER DI MADRASAH IBTIDAIYAH MA’ARIF LABSCHOOL SINTANG - Ashifur Rozaq; Ubabuddin Ubabuddin; Sri Sunantri (ADIBA : JOURNAL OF EDUCATION, 2022)
This research departs from the phenomenon of declining character values ​​in the world of education. Differences that arise in social life are often a source of conflict, due to the lack of tolerance in responding to diversity. Therefore, the character of tolerance that is instilled through the learning of moral aqidah to students needs to be pursued in order to create peace in the midst of diversity. The focus of this research is: 1) What are the character values ​​in Madrasah Ibtidaiyah Ma'arif Labschool Sintang? 2) What is the strategy of the teacher of moral aqidah in instilling character values ​​in Madrasah Ibtidaiyah Ma'arif Labschool Sintang? This research uses a qualitative approach and the type of case study. Data collection techniques through interviews, observation and documentation. Data analysis uses an interactive analysis model which includes data reduction, data display, and verification/drawing of conclusions. The results of the study show the following: 1) The character values ​​instilled in Madrasah Ibtidaiyah Ma'arif Labschool refer to the Character Education Strengthening (PPK) program established by the government, namely religious, nationalist, integrity, independent and mutual cooperation; 2) The strategy of teachers of Islamic faith in instilling character values ​​in madrasas is very varied, starting with using the PAIKEM strategy model, to internalizing the content of character values ​​in intracurricular, co-curricular and extracurricular activities.